THE MAKING OF TENSES COMPILATION VIDEO USED BY ALL CHARACTERS IN â€œPENGUINS OF MADAGASCARâ€ MOVIE TO LEARN GRAMMAR - Selvi Veronika; Muhammad Indra Gunawan (Politeknik Negeri Bengkalis, 2019)
The aim of this study was to make tenses compilation using a video in a film entitled Penguins of Madagascar. The method used in this study was a descriptive research. This video was created by using Adobe Premiere Pro CC 2017 program. There were several steps in making this video, including: collecting the materials, recording the voice, converting the files and editing the video The result of this study was a video of tenses compilation with English subtitle for learning English. The duration of the video was about ten minutes 40 second starting from the beginning until closing. There were pictures, audio, video and some informations about Penguins of Madagascar. This product is hoped to help students in learningÂ grammar especially tenses in easy way and fun and would become one of interesting teaching materials for English teachers in teaching English